2015
DOI: 10.1007/s13277-015-4131-6
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of the NEK6, AURKA, AURKB, and PAK1 genes in adenomatous colorectal polyps and colorectal adenocarcinoma

Abstract: Colorectal adenomatous polyp (CRAP) is a major risk factor for the development of sporadic colorectal cancer (CRC). Histone modifications are one of the epigenetic mechanisms that may have key roles in the carcinogenesis of CRC. The objective of the present study is to investigate the alternations in the defined histone modification gene expression profiles in patients with CRAP and CRC. Histone modification enzyme key gene expressions of the CRC, CRAP, and control groups were evaluated and compared using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Our data establishing AURKA as a substrate of VHL presents new opportunities for intervention, not only in RCC, but also in other cancers such as colorectal carcinoma, where genomic data from patients reveals the existence of VHL mutations, 48, 49 elevated AURKA 50 and ciliary defects. 51 Importantly, our demonstration that primary cilia can be rescued with AURKA and HDAC6 inhibitors provides proof-of-concept that targeting the VHL–AURKA–HDAC6 axis may have therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 75%
“…Our data establishing AURKA as a substrate of VHL presents new opportunities for intervention, not only in RCC, but also in other cancers such as colorectal carcinoma, where genomic data from patients reveals the existence of VHL mutations, 48, 49 elevated AURKA 50 and ciliary defects. 51 Importantly, our demonstration that primary cilia can be rescued with AURKA and HDAC6 inhibitors provides proof-of-concept that targeting the VHL–AURKA–HDAC6 axis may have therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 75%
“…Given these collective observations, we propose that the control of intracellular trafficking may be an ancient and conserved function for members of the NIMA kinase family. This would represent a role for mammalian NEK kinases that has been largely overlooked but could be relevant to their involvement in diseases including cancer and ciliopathies [23,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. Future studies in both C. elegans and mammalian systems will be important to establish the precise functions of NIMA-related kinases in cellular trafficking and human disease processes.…”
Section: Trafficking Functions Of Nima Kinase Family Members Are Likementioning
confidence: 99%
“…In recent years, altered expression and activity of NEK6 were associated with several types of cancer, such as liver [139], prostate [140], gastric [141][142][143], colorectal [144,145], breast [146], serous epithelial ovarian [147], thyroid [148], and retinoblastoma cancers [149]. In addition, inflammation-based diseases, such as ulcerative colitis, have also been linked to NEK6 [28].…”
Section: Nek6mentioning
confidence: 99%
“…The main risk factor for the development of colorectal adenocarcinoma (CRC) is the emergence of colorectal adenomatous polyps (CRAP), which are benign tumors that can progress to cancer through various genetic and epigenetic changes [144]. Kasap et al (2016) identified that NEK6 and other genes, such as AURKA, AURKB, HDAC1, and PAK1, are significantly overexpressed in samples from patients with CRC and CRAP. In addition, larger diameter polyps showed greater overexpression of NEK6 compared to smaller polyps [145].…”
Section: Nek6mentioning
confidence: 99%
See 1 more Smart Citation